ANALISIS PAKSAAN NIKAH DALAM PRAKTIK REK SEREK DI DESA KATOL BARAT KECAMATAN GEGER KABUPATEN BANGKALAN - Nurul Mahmudah; Ja'far Shodiq; Syamsul Arifin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2023)
Forced marriage by the village head has apposed 26th subsection in Peraturan Daerah (the Regional Regulation) Number 6 of 2014 concerning the Village that the village head has no authority of forcing the marriage and Article 6 paragraph (1) Law Number 1 of 1974 concerning Marriage that forbids marriage forced and must get agreement from brides. But this practice has been done for a long time ago and have supported by the societies of Katol Barat people. This research has been classified into field research. Used data is primary. The process of gathering data use the interview method. The data has been analyzed by descriptive qualitative method. Checking the validity of the data is done by using the technique of triangulation. The result of the research shows: (1) in the perspective of progressive law, marriage forced in the rek serek case is suitable with principles of progressive law, (2) in sadd al-dzari’ah perspective, marriage forced in the rek serek case is as mediation for behavior that has benefit. Because of that, the realization of it must be supported, and (3) a comparison between progressive law and sadd al-dzari’ah (prevent harm) includes the similarities and the differences. Progresif law and sadd al-dzari’ah have an equation to appear the benefit for people and go off the mainstream of laws. The difference between both is placed in the ontology, epistemology, and axiology area